Síntese de cromenodiidropiridinas via reação de Hantzsch catalisada por um líquido iônico superácido de função específica - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
A multicomponent synthesis Hantzsch type is an important methodology for formation of active dihydropyridines and also in getting chromenedihydropyridines. The latter can be accomplished by the reaction of two equivalents of β-ketoester, one equivalent of primary amine and 1 equivalent of salicylaldehyde. The importance of the synthesis must biological activity that can play chromenes and dihydropyridines: antitubercular, calcium channel blockers, anti-cancer, anti-HIV, etc. The fusion with the pyridinium nucleus chromene core through a multicomponent process is an attractive means as it reduces the number of reaction steps to form complex molecules such as chromenedihydropyridines in one step. The synthesis of chromenedihydropyridines via Hantzsch reaction is already reported in the literature by using acetic acid as catalyst. However a methodology will be developed using a new ionic liquid catalyst superacid specific function. The two compounds synthesized in this work were obtained using the best reaction conditions: etill 2,4-dimethyl-5-oxo-3,10b-dihydro-5H-chromeno [3,4-c] pyridine1-carboxylate with in 37% yield and ethyl 5,10b-dihydro-2,4-dimethyl-3- (4- nitrophenyl) -5-oxo-3H-chromeno [3,4-c] pyridine-1-carboxylate in 13 yield %.
Keywords: Reação de Hantzsch; Líquido iônico; Cromenodiidropiridinas; Hantzsch reaction; Ionic liquid; Chromenedihydropyridines; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA